Efficacy and safety of small-molecule TKIs in neoadjuvant treatment of HER2-positive breast cancer: a systematic review and network meta-analysis - Chaoyang Wang; Dong Xiao; Chao Zhai (BMC Cancer)
Abstract Objective This study aimed to evaluate the efficacy and safety of small-molecule TKIs in neoadjuvant treatment of HER2-positive breast cancer using a network meta-analysis approach. Methods A systematic literature search was conducted in the Medline, Embase, and Web of Science databases. Eligible studies that included HER2-positive breast cancer patients receiving neoadjuvant treatment with small-molecule TKIs before surgery were included. A Bayesian framework within a random-effects model was used for network meta-analysis to summarize direct and indirect evidence. Outcome measures included breast pathological complete response (breast pCR), total pathological complete response (total pCR) of the breast and lymph nodes, and selected safety endpoints. Results Eight eligible studies involving a total of 1,841 participants were included. The most common treatment regimens were Trastuzumab (n = 8), Lapatinib (n = 6), and Lapatinib plus Trastuzumab (n = 6), while there were fewer studies on Pyrotinib plus Trastuzumab (n = 2). No studies about tucatinib and neratinib were enrolled. The rankings of efficacy for the breast pCR and total pCR endpoints were as follows: (i) Pyrotinib plus Trastuzumab, (ii) Lapatinib plus Trastuzumab, (iii) Trastuzumab, (iv) Lapatinib. Regarding safety endpoints of grade 3 or higher diarrhea, neutropenia, fatigue, and skin disorders, the rankings were as follows: (i) Trastuzumab, (ii) Lapatinib, (iii) Lapatinib plus Trastuzumab, (iv) Pyrotinib plus Trastuzumab for diarrhea; (i) Pyrotinib plus Trastuzumab, (ii) Trastuzumab, (iii) Lapatinib plus Trastuzumab, (iv) Lapatinib for neutropenia; (i) Lapatinib plus Trastuzumab, (ii) Trastuzumab, (iii) Lapatinib for fatigue; (i) Trastuzumab, (ii) Lapatinib plus Trastuzumab, (iii) Lapatinib for skin disorders. Conclusion For HER2-positive breast cancer patients, the use of small-molecule TKIs in combination with trastuzumab as neoadjuvant treatment has certain advantages in improving the rate of pathological response. Dual-targeted therapy with pyrotinib shows objective efficacy and acceptable safety; however, further research is still needed to confirm these findings.